2019
DOI: 10.1080/21691401.2019.1652187
|View full text |Cite|
|
Sign up to set email alerts
|

Silencing circular ANRIL protects HK-2 cells from lipopolysaccharide-induced inflammatory injury through up-regulating microRNA-9

Abstract: Circular antisense non-coding RNA in the INK4 locus (cANRIL) participated in inflammation of endothelial cells. However, whether cANRIL is associated with inflammatory injury of HK-2 cells, thereby affecting chronic kidney disease has not been investigated. We tested the hypothesis that cANRIL participated in inflammatory response in vitro. HK-2 cells were stimulated by lipopolysaccharides (LPS). RT-qPCR was executed for cANRIL expression assessment. After transfection, cell viability, apoptosis, inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Another research indicated that CDKN2B-AS1 decreased the protective role of Rhein via elevating inflammation response in uric acid nephropathy rats [32]. Deng et al suggested that CDKN2B-AS1 knockdown reduced the inflammation response of lipopolysaccharide-treated HK-2 cells via increasing miR-9 expression [33]. Herein, CDKN2B-AS1 silencing decreased viability, ECM accumulation, inflammation response, and induced cell cycle arrest of HG-induced HMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Another research indicated that CDKN2B-AS1 decreased the protective role of Rhein via elevating inflammation response in uric acid nephropathy rats [32]. Deng et al suggested that CDKN2B-AS1 knockdown reduced the inflammation response of lipopolysaccharide-treated HK-2 cells via increasing miR-9 expression [33]. Herein, CDKN2B-AS1 silencing decreased viability, ECM accumulation, inflammation response, and induced cell cycle arrest of HG-induced HMCs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inhibition of NF-κB activation was shown to reduce cerebral ischemic injury in CI/R rats, which can be attributed, at least in part, to the reduction of inflammation and apoptosis following ischemic injury [32]. It has been reported that silencing of circ_ANRIL protects HK-2 cells from lipopolysaccharide (LPS)-induced inflammatory damage by inhibiting the activation of the NF-κB and c-Jun N-terminal kinase (JNK)/p38 pathways [33]. Here, our results also revealed that silencing of circ_ ANRIL inhibited the activation of the NF-κB pathway in OGD/R-induced HBMECs by sponging miR-622.…”
Section: Discussionmentioning
confidence: 99%
“…The oxidative damage induced by thrombosis in patients with AF is a hot topic in recent years. Studies have found that lncRNA ANRIL can induce thrombosis in the following ways: (a) LncRNA ANRIL can induce DNA damage in endothelial cells under oxidative stress and plays an important role in the occurrence and development of endothelial inflammation 24 . (b) A large number of studies have pointed out that under oxidative stress, lncRNA ANRIL can promote the release of myeloperoxidase, and can induce the body to produce a variety of free radicals, promote the formation of cardiovascular plaques, and induce thrombosis 25 .…”
Section: Discussionmentioning
confidence: 99%